Novel TNC-PDGFD fusion in fibrosarcomatous dermatofibrosarcoma protuberans: a case report - Yuan Chen; Ying-zhou Shi; Xiao-he Feng; Xiao-tong Wang; Xiang-lei He; Ming Zhao (BMC, 2021)
Abstract Background Dermatofibrosarcoma protuberans (DFSP) is a superficial fibroblastic tumor characterized by high rate of local recurrence and low metastatic potential. Fibrosarcomatous transformation can rarely arise in DFSP either de novo or as recurrent, which represents a form of tumor progression and carries an increased risk of metastasis over classic DFSP. Cytogenetically, DFSP is characterized by a recurrent unbalanced chromosome translocation t (17;22)(q22;q13), leading to the formation of COL1A1-PDGFB fusion transcript that is present in more than 90% of cases. Alternative fusions involving the PDGFD with partners of COL6A3 or EMILIN2 have recently been documented in less than 2% of cases. Herein, we report a DFSP with fibrosarcomtous morphology harboring a novel TNC-PDGFD fusion. Case presentation A 54-year-old female presented with a slowly growing mass in the right thigh. Excision demonstrated a 2-cm ovoid, well-circumscribed, gray-white, mass. Microscopic examination revealed a partially encapsulated subcutaneous nodule without dermal connection. The neoplasm was composed of cellular and fairly uniform spindle cells with brisk mitoses, arranged in elongated fascicles and herringbone patterns, with focal collagenized stroma. The neoplastic cells were positive for CD34 and smooth muscle actin. Fluorescence in-situ hybridization analyses showed negative for COL1A1-PDGFB fusion as well as NTRK1/2/3 rearrangements. A subsequent RNA sequencing detected an in-frame fusion between exon 15 of TNC and exon 6 of PDGFD. This fusion was further confirmed by nested reverse transcription polymerase chain reaction amplification followed by Sanger sequencing. A diagnosis of fibrosarcomatous DFSP was rendered and the patient was in good status at a follow-up of 12 months after the operation. Conclusions We report a fibrosarcomatous DFSP with novel TNC-PDGFD fusion, which adds to the pathologic and genetic spectrum of PDGFD-rearranged DFSP.